2015
DOI: 10.1142/s0219877015500054
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Determinants and Interaction Quality Effects on Tourists' Intention to Use Mobile Tourism Guide

Abstract: This study investigates model of tourist intention in the context of mobile tourism guide (MTG). We extend the innovation diffusion theory with the interaction quality construct. Partial least squares is used for data analysis. The results show four innovation characteristics such as relative advantage, compatibility, complexity and trialability significantly related to international tourists' intention to use MTG. Furthermore, the interaction quality has an impact on the relationship between lack of complexit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…On the other hand, the hypothesis (H 3 ) on the significant and positive relationship between perceived compatibility and intention to use in this study was supported, which confirmed the findings of prior studies ( 20 , 57 , 76 , 77 ). The current research offered empirical evidence for future eDoctor app research.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, the hypothesis (H 3 ) on the significant and positive relationship between perceived compatibility and intention to use in this study was supported, which confirmed the findings of prior studies ( 20 , 57 , 76 , 77 ). The current research offered empirical evidence for future eDoctor app research.…”
Section: Discussionsupporting
confidence: 91%
“…3 In the tourism industry, information technology has also been developed for the travel and tourism sector. 4 The tourism sector is able to produce about 11% of gross domestic product and employs 200 million people and serving tourists 700 million people worldwide. 5 Surakarta is an autonomous region with the city status under the Central Java province has many tourist attractions.…”
Section: Introductionmentioning
confidence: 99%